Mapa de unidades geomorfológicas de la zona occidental del cantón Gonzanamá, provincia de Loja, Ecuador; escala 1: 10.000. - Conza Chamba, Hugo Jhonatan (2019)
The present research work called “Map of Geomorphological Units of the western zone of the Gonzanamá canton, Loja province, Ecuador; scale 1: 10,000”, was aimed at defining the geomorphological units of the study area, through the use of geographic information systems (GIS). To achieve the stated objectives, it has been based on the method set forth by the Ecuadorian Space Institute and a variation of the International Institute for Aerospace System (ITC-Netherlands), which constitute a very efficient methodology for the elaboration of geomorphological cartography, so that through the DEM, it allows us to perform an automatic classification, in the Envi 5.3 software, generating a morphometric map ready to be assigned the different attributes. The determination of each of the geomorphological units, were performed by 3D digital photointerpretation, through the Digital Elevation Model, in the Arcgis 10.5 software and its extensions, this type of processing has allowed us to obtain a qualitative and quantitative analysis of each geomorphological unit considering the hierarchical level, genesis, morphometry, morphology, and its lithology as main components for an effective classification. The result of digital photointerpretation in the study area is 47 types of geoforms, which correspond to 5 genetic groups, among which we have: Fluvial with 1054 has equivalent to 2.7% of the total area, it is encompassing geoforms such as, plain of flood, low terrace and current channel, channeling, middle terrace, high terrace, slope or abrupt terrace, spreading cone surface, spreading cone abrupt. We also have slopes that cover an area of 21985 ha equivalent to 56% of the total, including geoforms such as: slopes, dented morphology, fault escarpments, erosional escarpment, triangular facets, recent and ancient colludes, slippery mace deposits. The Structural units are occupying an area of 4150 ha, which is equivalent to 10.65% of the total, including geoforms, slope surface, slope facing, structural surface remains, monoclinal hills, wavy reliefs. The Tectonic-structural genetic group, occupies an area of 10098 ha equivalent to 25% of the total area, includes geoforms such as: hill reliefs that range from very low to hilly hill reliefs, peaks and rocky outcrops. Finally, we have the Polygenic units that cover an area of 1774 ha, which is equivalent to 4.55%, within this group there are geoforms such as: recent and ancient alluvial colluvium, erosion surface, erosion surface slope, dissected erosion surface, inclined surface, steep inclined surface, witness hill, and interfluvium of narrow and rounded tops. To complement the study, the mass movements found in the area have been surveyed, as well as the field verification of each of the geoforms and geological formations described in the photointerpretation, so that this research contains a high degree of reliability of established data. The results obtained in this project, due to its scale, will allow an adequate management of the geomorphological cartography of the study area, in such a way that it serves as a basis for the elaboration or at the same time update of Development Plans and Territorial Planning.